Pomacea canaliculata hemocyanin as a novel natural immunostimulant in mammals - Chiumiento, Ignacio Rafael; Tricerri, María Alejandra; Cortéz, María Fernanda; Ituarte, Santiago; Tau, Julia; Mariño, Karina Valeria; Smaldini, Paola Lorena; Heras, Horacio; Dreon, Marcos Sebastián (Frontiers in Immunology, 2025)
IntroductionGastropod hemocyanins are potent immunostimulants in mammals, a trait associated with their large molecular size and unusual glycosylation patterns. While the hemocyanin from the marine snail keyhole limpet (KLH), has been widely studied and successfully employed as a carrier/adjuvant in several immunological applications, as well as a non-specific immunostimulant for bladder cancer treatment, few other gastropod hemocyanins have been biochemically and immunologically characterized. In this work, we investigated the immunogenic properties of the hemocyanin from Pomacea canaliculata (PcH), an invasive south American freshwater snail. This species, known for its high reproductive rate and easy rearing, represents a promising source of potential biomedical compounds, including hemocyanin.MethodsEmploying flow cytometry, fluorescence microscopy, immunoassays, and quantitative PCR, we analysed the effects of PcH on THP-1 monocytes and their derived macrophages, as well as its ability to induce humoral response on C57BL/6 mice. Additionally, we evaluated the structural stability of PcH across a wide range of temperature and pH values.Results and discussionOur findings demonstrate that PcH is a structurally stable protein that not only triggers a pro-inflammatory effect on THP-1 derived-macrophages by increasing IL1-β and TNF-α levels, but also promotes phenotypic changes associated with the monocyte-to-macrophage differentiation. Moreover, the humoral response induced by PcH in mice was indistinguishable from that of KLH, highlighting the promising immunostimulatory properties of this freshwater snail hemocyanin.